IMPLEMENTASI KEBIJAKAN PENGENDALIAN DEMAM BERDARAH DENGUE DI KOTA SEMARANG - Rafica Sari Andriani; Herbasuki Nurcahyanto; Slamet Santoso (Journal of Public Policy and Management Review, 2013)
The one of infectious diseases in Indonesia is Dengue Fever or. It is a disease causedby dengue virus and transmitted through mosquito Aides Aigepty. The most cases of denguefever in Central Java occurred in Semarang. The problems of the implementation of thispolicy caused by indecision on the application of sanctions in the implementation of policyabout restraining the dengue fever, the lack of human resources in preventive measures aboutthis disease, public awareness of PSN 3M Plus are lacking, and the limited budget to get arestraint of the implementation of policy about preventing this disease. The purpose of thisresearch is to analyze the implementation of policy about restraining dengue fever inSemarang through 4 variables above.This research is an observational research with data are descriptive qualitative. Thedata was collected through depth interviews with key informants, the Section Chief of P2B2,P2B2 staff, community leaders, jumantik, and the society of Semarang. This research aimedto analyzed the implementation of policy for preventing the dengue which can be seenthrough the phenomena that was occurring in the implementation of this policy, and thedeterminant factor of success of the implementation of this policy.The result of this research is the determinant factors in the implementation of thispolicy considered the Health Office of Semarang are caused by 4 variables, i.e. thecommunication which had transmitted properly to the society and clear, the quality of humanresources is good enough, the financial resources are lacking, the disposition which walkedproperly, and there were still mismatch with the SOP.